Identification and Characterization of DM1 Patients by a New Diagnostic Certified Assay: Neuromuscular and Cardiac Assessments. (9th May 2013) - Valaperta, Rea; Sansone, Valeria; Lombardi, Fortunata; Verdelli, Chiara; Colombo, Alessio; Valisi, Massimiliano; Brigonzi, Elisa; Costa, Elena; Meola, Giovanni
Abstract : The expansion of the specific trinucleotide sequence, [CTG], is the molecular pathological mechanism responsible for the clinical manifestations of DM1. Many studies have described different molecular genetic techniques to detect DM1, but as yet there is no data on the analytical performances of techniques used so far in this disease. We therefore developed and validated a molecular method, " Myotonic Dystrophy SB kit, " to better characterize our DM1 population. 113 patients were examined: 20 DM1-positive, 11 DM1/DM2-negative, and13 DM1-negative/DM2-positive, who had a previous molecular diagnosis, while 69 were new cases. This assay correctly identified 113/113 patients, and all were confirmed by different homemade assays. Comparative analysis revealed that the sensitivity and the specificity of the new kit were very high (>99%). Same results were obtained using several extraction procedures and different concentrations of DNA. The distribution of pathologic alleles showed a prevalence of the "classical" form, while of the 96 nonexpanded alleles 19 different allelic types were observed. Cardiac and neuromuscular parameters were used to clinically characterize our patients and support the new genetic analysis. Our findings suggest that this assay appears to be a very robust and reliable molecular test, showing high reproducibility and giving an unambiguous interpretation of results.